Transformasi Digital berbasis Smart Port Revolution di Pelabuhan Tanjung Emas: Optimalisasi Logistik melalui Terminal Booking System - Lubis, M. Daffa Fahada (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
This study examines the impact of the Terminal Booking System (TBS) implementation as part of the digital transformation at Tanjung Emas Port in Semarang, focusing on optimizing logistics efficiency. The main issues raised are high dwelling time, inefficiency of conventional logistics systems, and the lack of integration of the port's digital infrastructure, which leads to high logistics costs and a decline in regional export-import competitiveness. This study applies an explanatory quantitative method with an annual time series from 2014–2024. The analysis was conducted using multiple linear regression, moderated regression analysis (MRA), and the Autoregressive Distributed Lag (ARDL) model to examine the dynamics of long-term and short-term relationships between variables. The results show that the implementation of TBS significantly improves logistics efficiency, reflected in the increase in the Logistics Performance Index. However, dwelling time is not proven to be a significant moderator in strengthening the influence of TBS on logistics efficiency. Policy recommendations include accelerating the integration of TBS into the entire port system, developing a single-window-based integrated logistics platform, and implementing automation technology. Research confirms that successful digital transformation requires policy synergy, infrastructure investment, and strengthened cross-agency coordination to create Tanjung Emas Port in Semarang as a smart port that is efficient and highly competitive at the national level.